Kinetics and mechanism of oxygen desorption from anodized polycrystalline platinum electrodes under open circuit in carbon monoxide saturated 1 M perchloric acid - Bilmes, Sara Aldabe (1984)
The open circuit potential decay of polycrystalline platinum electrodes which were previously anodized in 1 M perchloric acid saturated with carbon monoxide is studied. The amount of electroadsorbed oxygen is measured by combining the potential decay measurements with electroreduction voltammograms. The kinetics of the open circuit anode potential decay are interpreted in terms of a Langmuir-Hinshelwood-type mechanism where two simultaneously adsorbed species, namely oxygen atoms and linear carbon monoxide, are involved.